'If an apple is a foreign apple you have to wash it very carefully': Youth discourses on racism. (November 2016) - Alemanji, Aminkeng A; Dervin, Fred
This study offers a critique of the questions used in anti-racism discourse and education. It discusses the dangers of asking whether a person or group is racist and the possible consequences such questions could have on people's discourses and attitudes. Reactions or responses to the questions can vary from anger, defence of self against other, denial of racism and/or a strong far-right nationalistic feeling. The questions examined in this study were used in a workshop about racism in Finnish upper secondary schools. Our main interest lies in examining how questions produce or affect discourses, particularly the kinds of discourses that arise as the students reflect and respond to these questions in small groups. By analysing these discourses, we are able to get an insight into how students construct an understanding of racism vis-à-vis the issues of nationality, family, self and others. Our findings are suggestive of the fact that students' understanding of racism is often limited to individual acts of racism rather than an understanding of racism as a system of oppression. The article calls for the need to reassess the questions used in anti-racism discourse or education that do not necessarily lead to progressive discourse on the issue of racism. We also call for teachers using these questions to closely follow up how students interpret and discuss the topic of racism.